Ca(OH)2 Pre‐Treated Bentonite for Phosphorus Removal and Recovery From Synthetic and Real Wastewater. Issue 2 (15th January 2018) - Markou, Giorgos; Mitrogiannis, Dimitris; Inglezakis, Vassilis; Muylaert, Koenraad; Koukouzas, Nikolaos; Tsoukalas, Nikolaos; Kamitsos, Efstratios; Palles, Dimitrios; Baziotis, Ioannis
Abstract : The performance of chemically pre‐treated bentonite with Ca(OH)2 toward ortho‐phosphate phosphorus (OPP) removal efficiency in synthetic (inorganic) and real (anaerobically digested effluents) wastewater (WW) is evaluated. The Ca(OH)2 pre‐treated bentonite displays a significant increase of OPP uptake ( q e ; mg P g −1 bentonite) of 40 and 15 times, reaching about 14 and 5.5 mg P g −1 for synthetic and real WW, respectively. The optimum pH for OPP sorption is 7, while at higher pH values, although OPP removal is high due to the precipitation in the liquid phase, the OPP removal in solid phase, that is, sorption onto bentonite surface is less compared to pH 7. Scanning electron microscopy (SEM) and X‐ray diffraction (XRD) analysis shows that OPP forms various complexes with co‐existing ions in WW, such as apatite (with Ca 2+ ) and struvite (with N H 4 + and Mg 2+ ). The most influential parameter of the pre‐treatment is the dosage of Ca(OH)2 . Concentration of 0.5 M Ca(OH)2 or higher is necessary for an efficient pre‐treatment. In contrast, the concentration of bentonite does not affect the pre‐treatment efficiency, and a mass of 500 g L −1 bentonite is found to be sufficient. The chemical pre‐treatment with Ca(OH)2 renders bentonite a promising low‐cost sorbent for OPP removal and recovery from WW. Abstract : Recovery of phosphorus from wastewater is of particular importance for sustainable agriculture. In this study, the performance of Ca(OH)2 pretreated bentonite for phosphorus adsorption from wastewater is investigated. Ca(OH)2 pretreatment of bentonite increases its adsorption capacity, reaching 14 and 5.5 mg P g −1 for synthetic and real wastewater, respectively. Adsorption of phosphorus with pretreated bentonite is a promising technology.